Transformasi Nilai Huyula Ambu, Eya Dila Pito-Pito’o, dan Delo Tutumulo Lambi dalam Pendidikan Akuntansi Syariah - Mohamad Anwar Thalib; Roni Mohamad (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Purpose: This study aims to explore and transform the values of Gorontalo's local wisdom (huyula ambu, eya dila pito-pito’o, and delo tutumulo lambi) into Islamic accounting education. This research is motivated by the dominance of technical, calculative, and administrative aspects in Islamic accounting education, which tends to neglect the social and spiritual dimensions. Method: The research method used is qualitative with a netnographic approach. The data was obtained from three environmental care action videos uploaded by the Tanggidaa Group on TikTok, which received high interaction from netizens. Netizen comments and responses were analyzed thru the stages of reduction, presentation, and drawing conclusions Results: This study found that the environmental care actions were rich in the values of huyula ambu, eya dila pito-pito'o, and delo tutumulo lambi, which were manifested in cooperation, prayer, and a sense of pride. Implications: These values can be transformed into Islamic accounting education thru field observation assignments (huyula), ethics case studies with religious reflection (eya dila pito-pito'o), and analysis of the social benefits of financial statements (delo tutumulo lambi). Theoretically, this research expands the paradigm of Islamic accounting education by asserting that accounting learning should not only be oriented toward technical skills, but must also cultivate social awareness, spirituality, and local cultural wisdom as an integral part of Islamic accounting practice. Novelty: The novelty of this research lies in the integration of Gorontalo's local wisdom into the Islamic accounting curriculum.